1990
DOI: 10.21273/hortsci.25.11.1443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recent Enrollment Trends and Recruiting Strategies in Horticulture

Abstract: A survey of bachelor degree programs in the United States indicated that horticultural enrollment declined 4.4% between 1986 and 1988. Programs that increased enrollment (39% of those responding) were more likely to use various recruitment materials and activities than were those with declining or no change in enrollment (48% and 13%, respectively). Supply of students and time required to recruit were most often reported as high priority issues. The percentage of new majors recently graduated from high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…cultivation of these species-all of these factors can be incorporated into horticultural education programs. This is particularly relevant as plant science programs continue to experience decreasing or flat enrollment (Darnell and Cheek, 2005;McCallister et al, 2005;Rhodus, 1990) and face pressure to bring in more students. Although students were able to identify areas where FNWs occur with little trouble and claimed to be able to identify by sight a good number of FNWs, their ability to accurately identify flowering season for FNWs was skewed compared with reported flowering season (Table 2; Bell and Taylor, 1982;Taylor, 1998;Wildflower Seed and Plant Growers Association, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…cultivation of these species-all of these factors can be incorporated into horticultural education programs. This is particularly relevant as plant science programs continue to experience decreasing or flat enrollment (Darnell and Cheek, 2005;McCallister et al, 2005;Rhodus, 1990) and face pressure to bring in more students. Although students were able to identify areas where FNWs occur with little trouble and claimed to be able to identify by sight a good number of FNWs, their ability to accurately identify flowering season for FNWs was skewed compared with reported flowering season (Table 2; Bell and Taylor, 1982;Taylor, 1998;Wildflower Seed and Plant Growers Association, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A good way to increase awareness and interest in different careers is to provide positive experiences for youth (Crombie et al, 2003) since students look to their experiences when developing both educational and occupational plans (Odell, 1988). Rhodus (1990) found that career-influencing events increase enrollment in horticulture programs, even when the increase in enrollment might not be seen for a few years. One way to introduce students to career opportunities in the sciences is to engage them in summer science programs before their college years.…”
mentioning
confidence: 99%
“…A rapidly growing world population needs horticulturists to produce more food with fewer resources and to improve the nutritional content of horticultural crops [American Society for Horticultural Science (ASHS), 2014]. However, student populations in horticulture departments have continued to decrease in the past few decades (Hewett, 2015;Lower, 1991;Palmer, 2004;Rhodus, 1990). Some of the decline is due to common worldwide perceptions that horticulture is primarily manual work, not requiring postsecondary education (Palmer, 2004).…”
mentioning
confidence: 99%
“…of Delaware's procedure for recruiting students into a graduate program in garden administration. Rhodus (1990) reported considerable effort on the part of individual schools using many tools and approaches, but cited no collaborative efforts and no national focus. National ASHS educational forums (Albrecht, 1990;Stack, 1989) and industry publications (Hundley, 1988;Meister, 1989) have addressed the challenge of student recruitment and have suggested the need for a national effort.…”
mentioning
confidence: 99%